2017
DOI: 10.1159/000479943
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Restless Legs Syndrome Pleads “Not Guilty”

Abstract: there was no significant association between RLS and 3-year mortality, either with age and gender as covariates [6] .In the current issue of the American Journal of Nephrology , an unprecedented 15-year follow-up of RLS survivorship is presented by Baiardi et al. [7] . These investigators demonstrate that RLS-HD patients had a lower mortality rate compared to those HD patients without the syndrome (63.8% [4.3%/year] RLS-HD vs. 87.6% [5.8%/year] non-RLS HD, p = 0.04). Similarly, the mortality rate was not influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Takaki et al reported that RLS is significantly associated with higher anxiety prevalence in hemodialysis patients [13]. On the other hand, Sakkas et al found that although RLS is associated with other morbidities, it does not affect the mortality rate in ESRD patients and still the cardiovascular cause is the first contributor to the mortality rate in ESRD [28]. The same results were reported in a study by Baiardi et al conducted on 128 ESRD patients on hemodialysis [29].…”
Section: Complications Of Rls and Its Effect On Patient's Lifementioning
confidence: 62%
“…Takaki et al reported that RLS is significantly associated with higher anxiety prevalence in hemodialysis patients [13]. On the other hand, Sakkas et al found that although RLS is associated with other morbidities, it does not affect the mortality rate in ESRD patients and still the cardiovascular cause is the first contributor to the mortality rate in ESRD [28]. The same results were reported in a study by Baiardi et al conducted on 128 ESRD patients on hemodialysis [29].…”
Section: Complications Of Rls and Its Effect On Patient's Lifementioning
confidence: 62%